Serious Hemorrhagic Complications After Successful Treatment of Hematopoietic Stem Cell Transplantation-Associated Thrombotic Microangiopathy With Defibrotide in Pediatric Patient With Myelodysplastic Syndrome - Laberko, Alexandra; Aksenova, Marina; Shipitsina, Irina; Khamin, Igor; Shcherbina, Anna; Balashov, Dmitry; Maschan, Alexei (Frontiers in Pediatrics, 2020)
Background: Transplant - associated thrombotic microangiopathy (TAM) is a life-threating complication of hematopoietic stem cell transplantation (HSCT). There is some evidence of endothelial injury playing significant role in TAM development. The efficacy of defibrotide was demonstrated for prophylaxis and treatment of another HSCT-associated endothelial damage syndrome – liver veno-occlusive disease. The data for defibrotide usage in TAM are limited. Case description: A nine-year old boy underwent HSCT from a matched unrelated donor for monosomy 7-associated myelodysplastic syndrome treatment. A myeloablative preparative regimen and post-transplant immunosuppression with cyclophosphamide days +3 and +4 and a combination of tacrolimus with mycophenolate mofetil from day +5 were used. From day +61, sustained fever with progressive neurologic impairment and no evidence of infection was observed. On day +68 the patient developed severe TAM with acute kidney injury requiring renal replacement therapy. Defibrotide therapy 25mg/kg/d was administered for 7 days with resolution of TAM symptoms. It was followed by multiple haemorrhagic episodes – epistaxis, haemorrhagic cystitis and renal hemorrhage, which are presumed to be the complications of defibrotide therapy. Conclusion: Defibrotide could be an effective therapy for TAM, but adequate doses, duration of therapy and drug safety profile both for paediatric and adult patients need to be evaluated by randomised prospective studies.